An Empirical Event Study on Possibilities to Earn Superior Risk Adjusted Returns of Selected Stocks by Trading on Earning Announcement - Jayaraman, R.; Ramarathinam, M. S.; Ganapathy, K. N. (Indian Journal of Finance, 2011)
The efficient Performance of a particular stock in the market can be measured in several ways and means. The capital gain of a stock will be the major determinant of the performance of a stock. Any stock, which generates more quantum of capital gain, that stock is considered to be the efficient stock? If any market, which possesses efficient stocks, that market is considered to be the efficient market. In other words, an efficient market is one in which the market price of a security is an unbiased estimate of its intrinsic value. Market efficiency is defined in relation to information that is reflected in security prices. Market efficiency can be segregated into three levels - they are weak-form efficiency, semi-strong-form efficiency and strong-form efficiency. In the weak-form efficiency, the prices of a stock reflect all information found in the record of past prices and volumes. Whereas in the semi-strong-form efficiency, the prices of a particular stock reflect not only all information found in the record of past prices and volumes, but also all other publicly available information. In the strong-form efficiency, the stock prices reflect all available information, public as well as private. This paper focuses on the semi-strong-form efficiency of SBI and HDFC bank stocks. So, to examine the semi-strong-form efficiency of SBI and HDFC bank stocks, the Rate of return of the selected stocks were taken for fifteen days from the date of announcement of dividend and the run test was applied separately and together on the Rate of returns of the selected bank stocks. The result shows that there is no impact of announcement of dividend over the rate of return of State Bank of India and HDFC Bank stocks from the date of declaration of dividend.